RETRACTED: STRENGTHENING INDONESIAN NATIONAL IDENTITY THROUGH HISTORY SEMARANG AS A MARITIME CITY: A MEDIUM OF UNITY IN DIVERSITY - Yuliati, Dewi (HUMANIKA, 2013)
Artikel  ini telah ditarik dari jurnal Humanika Vol. 18  No 2 tahun 2012.Silakan merujuk artikel STRENGTHENING INDONESIAN NATIONAL IDENTITY THROUGH HISTORY SEMARANG AS A MARITIME CITY: A MEDIUM OF UNITY IN DIVERSITY  pada link berikut: https://globaljournals.org/item/2992-strengthening-indonesian-national-identity-through-history-semarang-as-a-maritime-city-a-medium-of-unity-in-diversity